Gods beneath the ice - Kennington, Alexandra (The blood & souls duology, 2026)
"Revna knew ruling would be difficult, but she never anticipated ruling with a newfound Lurae. The godtouched fear her, the godforsaken don't trust her, and her best friend doesn't know the truth she's been hiding. When the war-ending treaty is signed, Revna will reveal her secrets and finally put the Hellbringer behind her. Except the Kryllian Queen refuses to sign the treaty when she discovers how volatile Revna's bloodsinging is. Desperate for any alliance, Revna begrudgingly agrees to the Queen's proposal: if Revna can learn to control her magic in three weeks, negotiations will resume. But there's a catch-the queen's general will be the one training her. Revna will work with the Hellbringer once more, but she won't make it easy. But when the general reveals that the dead are unable to pass on, they realize there's more at stake than their tangled relationship. Ancient, powerful secrets tie the realm-and Revna and the Hellbringer-together, and their only hope of lasting peace is to unweave them"-- Provided by publisher.